On a decimal currency - Galbraith, Joseph A. (Statistical and Social Inquiry Society of Ireland, 1853)
In many essays which have lately appeared on the subject of a decimal currency, the distinction has not been sufficiently observed which exists between a decimal coinage and a decimal currency; between a system of coins proceeding by decimal gradations, and a decimal system of denominations in moneys of account. It cannot be denied that a coinage founded on such a principle would be most convenient, if decimal denominations were once adopted; but it should be clearly understood that any coinage may be used consistently with a decimal system of accounts, provided that no piece shall contain a fractional part of the lowest denomination. In the United States of America, for example, where a decimal system prevails, the coins in common use are gold pieces of ten dollars, five dollars, and two and a half dollars, and silver pieces of one dollar, a half dollar, and a quarter dollar. In France and Belgium, where accounts are kept according to a decimal system, the gold coinage consists of pieces of ten francs, twenty francs, and twentyfive francs; the silver of pieces of five francs, two francs, francs, half-francs, and quarter-francs, which latter consist of 50 and 25 centimes respectively.
Read May 16th 1853
Keywords: Decimal currency; Coinage; 314.15